PROSPECTS OF USING PHYTOTHERAPY AT DISORDERS OF FAT AND CARBOHYDRATE METABOLISM - M. N. Povydysh; V. G. Luzhanin; D. Yu. Ivkin; M. V. Belousov; G. P. Yakovlev (Разработка и регистрация лекарственных средств, 2019)
The review describes the first stage of phyto-pharmacological screening. It includes literature data analysis on promising species of medicinal plant raw materials, total extracts and individual substances of plant origin with pronounced pharmacological activity in disorders of fat and carbohydrate metabolism, incl. obesity, diabetes mellitus type 2, metabolic syndrome, and non-alcoholic fatty liver disease, confirmed in preclinical and/or clinical trials.